2019
DOI: 10.1002/jmor.20992
|View full text |Cite
|
Sign up to set email alerts
|

Flipper bone distribution reveals flexible trailing edge in underwater flying marine tetrapods

Abstract: Hydrofoil-shaped limbs (flipper-hydrofoils) have evolved independently several times in secondarily marine tetrapods and generally fall into two functional categories:(1) those that produce the majority of thrust during locomotion (propulsive flipperhydrofoils); (2) those used primarily to steer and resist destabilizing movements such as yaw, pitch, and roll (controller flipper-hydrofoils). The morphological differences between these two types have been poorly understood. Theoretical and experimental studies o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 105 publications
0
16
0
Order By: Relevance
“…Dorsoventrally flattened limb bones are seen in the wings of various wing-propelled diving birds (penguins, volant auks, diving petrels and some shearwaters; Kuroda 1954 ; Storer 1960 ; Livezey 1988 , 1989 ), and are prevalent in the specialized limbs of many different groups of secondarily aquatic tetrapods (e.g., Thewissen and Taylor 2007 ; Kelley and Pyenson 2015 ). When limbs are employed as flapping hydrofoils, dorsoventrally flattened limb bones increase hydrofoil rigidity, enabling the production of increased thrust and improving propulsive efficiency (although hydrofoil flexibility is another crucial factor underlying propulsive efficiency; DeBlois and Motani 2019 ). Therefore, flattened wing bones in Mancallinae strongly indicate that they were structurally suited to aquatic flight in a manner presumably homologous with that in crown-group Alcidae, and analogous to that in other extant wing-propelled diving birds (as well as other aquatic tetrapods).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Dorsoventrally flattened limb bones are seen in the wings of various wing-propelled diving birds (penguins, volant auks, diving petrels and some shearwaters; Kuroda 1954 ; Storer 1960 ; Livezey 1988 , 1989 ), and are prevalent in the specialized limbs of many different groups of secondarily aquatic tetrapods (e.g., Thewissen and Taylor 2007 ; Kelley and Pyenson 2015 ). When limbs are employed as flapping hydrofoils, dorsoventrally flattened limb bones increase hydrofoil rigidity, enabling the production of increased thrust and improving propulsive efficiency (although hydrofoil flexibility is another crucial factor underlying propulsive efficiency; DeBlois and Motani 2019 ). Therefore, flattened wing bones in Mancallinae strongly indicate that they were structurally suited to aquatic flight in a manner presumably homologous with that in crown-group Alcidae, and analogous to that in other extant wing-propelled diving birds (as well as other aquatic tetrapods).…”
Section: Discussionmentioning
confidence: 99%
“…As such, both the elongated crista deltopectoralis and attachment site for the ligg. propatagiale et limitans cubiti appear to represent modifications to increase the rigidity of the leading edge of the wings, which would increase thrust production in aquatic flight ( DeBlois and Motani 2019 ). It is evident that these modifications were acquired independently in Pinguinus and Mancallinae ( Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several morphological attributes have been ascribed to wing-propelled diving: relatively small wings characterized by shortened bones and flight feathers which induce less drag and provide increased rigidity (Pennycuick 1987;Livezey 1988Livezey , 1989Louw 1992); dorsoventrally flattened wing bones with thick cortices apparently providing hydrodynamic efficiency and resistance to bending stress (Stettenheim 1959;Habib and Ruff 2008;Habib 2010; Clarke 2014); well-developed wing elevator muscles presumably involved in active upstroke of the wings in a dense, viscous medium (Stettenheim 1959;Schreiweis 1982;Bannasch 1986bBannasch , 1994Kovacs and Meyers, 2000); and reduced mobility of the elbow, wrist, and digital joints providing increased rigidity to the wings (specifically noted in penguins, but absent in volant auks; Bannasch 1986aBannasch , 1994Raikow et al 1988;Louw 1992). The specialized, rigid wings of penguins are often referred to as flippers, analogous to the 6 modified limbs of other secondarily aquatic tetrapods (e.g., Thewissen and Taylor 2007;Kelley and Pyenson 2015;DeBlois and Motani 2019). 101…”
Section: Introductionmentioning
confidence: 99%
“…Although they are not closely related, all these groups share something in common: their ancestors had fingers. Previous studies have suggested that the limb-to-forefin (to better distinguish it from pectoral fins) transition in aquatic tetrapods occurred several times and followed diverse strategies [6][7][8][9][10][11]. However, did that morphological shift influence their anatomical integration?…”
Section: Introductionmentioning
confidence: 99%